(untitled) (Jurnal Inovasi Sekolah Dasar, 2024)
This study aims to determine the influence of big book media on reading ability in Indonesian subjects of grade II students of SDN 101916 Araskabu. This research is a quantitative research using an experimental method with the type of Pre-Experimental Design with a One Group Pretest-Posttest Design design. The population is all second-grade students of SDN 101916 Araskabu for the 2023/2024 school year which totals 31 students. The sample in this study is total sampling, which is the same sample as the population with the number of class II students 31 students. Data collection was carried out using test techniques, namely score data obtained from students’ reading ability results collected using tests through reading, interviews, observation and documentation. Data analysis techniques are in the form of descriptive and inferential statistical analysis.The results of this study show that there is an influence of big book media on reading ability in Indonesian subjects of grade II students of SDN 101916 Araskabu, judging from the average score where the pretest score is 64.25 to 75.29 with the highest score of 100 obtained by 2 students and the lowest score is 37 obtained by 1 student. The calculation of the results of the hypothesis test showed that the value of tcount with ttable was obtained tcount > ttable, namely the value of 7.07>1.69, then the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted which means that there was an influence of big book media on reading ability in Indonesian subjects of second grade students of SDN 101916 Araskabu.